Innu materials, Selected materials, 1676-1930, on Indian linguistics - Laure, Pierre-Michel, 1688-1738; Faber, Bonaventura (1690)
Part of a collection comprised of religious and linguistic materials in various Native American languages. Many were written by Jesuit missionaries of New France. These particular items include a copy of a Montagnais dictionary attributed to Father Bonaventura Faber (or Favre) circa 1690; Montagnais prayers attributed to Father Pierre-Michel (or Petro) Laure, containing also a fragment of a letter dated 1724 noting "this is the third year that I live with the Tad8ssaciens," and denouncing the honesty and truthfulness of the Indians; and a register of baptisms, marriages, and deaths at La Mission du Domain du Roy from 1759 to 1774. Native peoples mentioned in the latter include Chicoutimi, Tadussaks, Mille Vaches, and Montagnais. Originals in the Archives de l'Archiveche de Quebec, Bibliotheque de l'Archeveche de Quebec, and Universite Laval, Seminaire de Quebec.